Pengaruh suhu sterilisasi pada sifat morfologis dan mekanik kemasan fleksibel retort produk empal gentong siap saji [The effect of sterilization temperature on morphological and mechanical properties of retort flexible packaging for ready to eat “empal gentong” product ] - Kusumaningrum, Annisa; Febrisiantosa, Andi; Amri, Aldicky Faizal; Amdani, Rima Zuriah; Nurhikmat, Asep; Prayogi, Siswo; Dewandaru, Bayu Murti (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
Thermal food sterilization is the preservation technology to extend packaged food shelf life. The properties of packaging materials that change after thermal sterilization are morphological, mechanical, and color properties. This study aimed to observe the effect of sterilization temperature on the morphological, mechanical, and color properties of flexible retort pouch packaging. The food product sample processed in retort packaging was Indonesian traditional food, “empal gentong”. The retort package was composed of PET/Al/Nylon/CPP and processed at 121 °C 0,8 bar for 9 min, with an unprocessed sample was as a control. Three replications of mechanical and color results were analyzed using T-test with p<0.05 significance level to determine the significant difference. The retort pouch sample showed visual and microscopic defects in the form of separation between the PET layer and aluminum foil after being processed at 121 °C 0,8 bar for 9 minutes. In addition, temperature processing at 121 °C influenced the tear strength results and color significantly (p<0,05). Color changes was occured on the inside of the packaging contacting with the food. Each layer in multilayer packaging is interrelated and supports one another. Multilayer flexible packaging combines the different properties of a single monolayer material, so it is suitable for commercial sterile food packaging.